(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity (PA) is essential for coronary heart disease (CHD) management, but German GPs seldom provide PA advice due to insufficient training. Guided by behavioural theory (i.e. COM-B model) and qualitative research with GPs and patients, we developed a 3.5-hour small-group training on 3As (ask, advise, assist) PA counselling. This pilot study evaluated study and training procedures, as well as the preliminary training effectiveness on GP counselling behaviour to inform a pragmatic cluster-randomised controlled trial (cRCT). Methods: Between 08/2024–10/2024, we conducted a pragmatic two-arm pilot cRCT in North Rhine-Westphalia, Germany. We randomised (1:1) GP practices to intervention (IG) and control group (CG). GPs of both groups received the 3.5-hour training including theoretical input, role-play, self-reflection, and practical materials. We surveyed patients with CHD (CG: five weeks before GP training; IG: five weeks after) via face-to-face questionnaires immediately after routine GP consultations. Outcomes included recruitment rates (aim: 10 GP practices, 120 patients/12 per practice), patient-reported PA discussion and 3As adherence (intention-to-treat), feasibility of randomisation and data collection processes, and acceptance of materials. A qualitative process evaluation with GPs and patients explored experiences and suggestions for refinement. Results: We randomised 11 GP practices (CG: n = 5; IG: n = 6 initially, one dropout leaving n = 5; with a total of 15 GPs), and collected data from 114 patients with CHD (CG: n = 52; IG: n = 62; 34% female, mean age 70 ± 12). Randomisation and data collection processes were largely feasible, with minor questionnaire and training material refinements recommended. Qualitative feedback indicated high acceptance of training content and organisation, and suggestions to specify some learning objectives. PA was discussed relatively more frequently with patients of the IG (68%, 95% confidence interval (CI): 55%–79%) than of the CG (33%, 95% CI: 20%–47%). Relatively more patients in the IG received PA advice following the 3As (ask: 65%, advise: 39%, assist: 56% vs. CG: 29%, 17%, 23%). Conclusions: The pilot confirms feasibility of recruitment, randomisation, and data collection for a full cRCT. It suggests that the training can increase GP-delivered PA discussions and adherence to the 3As. If confirmed in a larger trial, this structured intervention could facilitate sustainable integration of brief PA counselling into routine GP care. Support/Funding Source: German Ministry of Education and Research. Keywords: Brief advice, coronary heart disease, education, general practice, physical activity